Diagnóstico de salud bucodental y factores de riesgo en los centros educativos secundarios unidad educativa mushuk rimak, unidad educativa a distancia de loja ext. madre laura montoya de la parroquia rural San Lucas Del Cantòn Loja año 2013 - Ramos Vicente, Leticia Paola (2013)
The oral diseases are a major problem in our country and in the South Region, it represents an important index, so Loja Canton is not exempt from this reality in the rural and urban parishes. The research work carried out, has as its central goal perform the diagnosis of oral health of the pupils of the secondary education center "MushukRimak and Ext. Mother Laura Montoya" from the parish of St. Luke of the Canton Loja 2013. This project is descriptive, prospective, and transversal is working with 151 students in secondary education. In the San Lucas rural parish of the Loja canton, the adolescents of the educational had a 97.35 % percent of dental caries, 85.43% percent of gingival inflammation, and 85.43% percent of gingival bleeding and gingival recession of 33.1% .The pathologies the affect most frequently are anterior open bite 6.8%, 3.3 % deep bite and Bite to bisbis of 3.3%. The results were collected through a survey and History Dental Clinic, showing that the whole group examined had any abnormal in their mouth. Key words: Dental Caries, Gingival Inflammation, Risk Factors